Induction in myeloid leukemic cells of genes that are expressed in different normal tissues - Lotem, Joseph (National Academy of Sciences, 2004)
Using DNA microarray and cluster analysis of expressed genes in a cloned line (M1-t-p53) of myeloid leukemic cells, we have analyzed the expression of genes that are preferentially expressed in different normal tissues. Clustering of 547 highly expressed genes in these leukemic cells showed 38 genes preferentially expressed in normal hematopoietic tissues and 122 other genes preferentially expressed in different normal nonhematopoietic tissues, including neuronal tissues, muscle, liver, and testis. We have also analyzed the genes whose expression in the leukemic cells changed after activation of WT p53 and treatment with the cytokine IL-6 or the calcium mobilizer thapsigargin. Of 620 such genes in the leukemic cells that were differentially expressed in normal tissues, clustering showed 80 genes that were preferentially expressed in hematopoietic tissues and 132 genes in different normal nonhematopietic tissues that also included neuronal tissues, muscle, liver, and testis. Activation of p53 and treatment with IL-6 or thapsigargin induced different changes in the genes preferentially expressed in these normal tissues. These myeloid leukemic cells thus express genes that are expressed in normal nonhematopoietic tissues, and various treatments can reprogram these cells to induce other such nonhematopoietic genes. The results indicate that these leukemic cells share with normal hematopoietic stem cells the plasticity of differentiation to different cell types. It is suggested that this reprogramming to induce in malignant cells genes that are expressed in different normal tissues may be of clinical value in therapy.